Early stages of legume-rhizobia symbiosis are controlled by ABCG-mediated transport of active cytokinins - Jarzyniak, Karolina; Banasiak, Joanna; Jamruszka, Tomasz; Pawela, Aleksandra; Di Donato, Martin; Novák, Ondřej; Geisler, Markus; Jasiński, Michał (Nature plants, 2021)
Growing evidence has highlighted the essential role of plant hormones, notably, cytokinins (CKs), in nitrogen-fixing symbiosis, both at early and late nodulation stages1,2. Despite numerous studies showing the central role of CK in nodulation, the importance of CK transport in the symbiosis is unknown. Here, we show the role of ABCG56, a full-size ATP-binding cassette (ABC) transporter in the early stages of the nodulation. MtABCG56 is expressed in roots and nodules and its messenger RNA levels increase upon treatment with symbiotic bacteria, isolated Nod factor and CKs, accumulating within the epidermis and root cortex. MtABCG56 exports bioactive CKs in an ATP-dependent manner over the plasma membrane and its disruption results in an impairment of nodulation. Our data indicate that ABCG-mediated cytokinin transport is important for proper establishment of N-fixing nodules.
Keywords: Symbiosis; Plant Growth Regulators; Medicago truncatula; Cytokinins; Plant Proteins; Rhizobium; biologický transport; ABC transportér, podrodina G; regulátory růstu rostlin; symbióza; Nitrogen Fixation; rostlinné proteiny; ATP Binding Cassette Transporter, Subfamily G; fixace dusíku; Biological Transport; cytokininy